The role of hypnotherapy in evidence‐based clinical practice. (29th July 2016) - Griffiths, MJ
Abstract : The purpose of this review was to discuss the place of hypnotherapy in a modern medical world dominated by so‐called evidence‐based clinical practice. Hypnosis is an easily learned technique that is a valuable adjuvant to many medical, dental and psychological interventions.